Candidate modifier genes for immune function in 22q11.2 deletion syndrome. Issue 1 (12th December 2019) - Pinnaro, Catherina T.; Henry, Travis; Major, Heather J.; Parida, Mrutyunjaya; DesJardin, Lucy E.; Manak, John R.; Darbro, Benjamin W.
Abstract: Background: The 22q11.2 deletion syndrome (22q11.2DS) is the most common contiguous microdeletion affecting humans and exhibits extreme phenotypic heterogeneity. Patients can manifest any combination of comorbidities including congenital heart disease, hypoparathyroidism, cleft palate, kidney abnormalities, neurodevelopmental disorders, and immune dysfunction. Immunodeficiency is present in the majority of patients with 22q11.2DS and is the second leading cause of death in these patients. Knowing the genetic determinants of immune dysfunction will aid in prognostication and potentially novel treatments. Methods: We performed exome sequencing and gene‐based variant association analysis on 31 deeply phenotyped individuals with the canonical 3Mb 22q11.2 deletion to identify what genes outside the 22q11.2 locus may be modifying the immune dysregulated phenotype. Immunophenotyping was performed using preexisting medical data and a novel scoring system developed from numerous clinical laboratory values including immunoglobulin levels, lymphocyte transformation to antigens (LTA), lymphocyte transformation to mitogens (LTM), and peripheral blood flow cytometry. Immunophenotypic scoring was validated against newborn screening T‐cell receptor excision circle (TREC) results. Results: Rare DNA variants in transcriptional regulators involved in retinoic acid signaling ( NCOR2, OMIM *600848 and EP300, OMIM *602700) were found to be associated with immunophenotype. Conclusion: The expression of TBX1, which seems to confer the major phenotypic features of 22q11.2DS, is regulated via retinoic acid signaling, and alterations in retinoic acid signaling during embryonic development can lead to phenocopies of 22q11.2DS. These observations support the hypothesis that genetic modifiers outside the microdeletion locus may influence the immune function in 22q11.2DS patients. Abstract : We performed deep phenotyping for immune status on 31 individuals with the canonical 3Mb 22q11.2 deletion followed by whole exome sequencing. DNA variants in transcriptional regulators involved in retinoic acid signaling (NCOR2, EP300) were found to be associated with immune status.